Tipologia de parlants en una comunitat de parla amb interrupció de la transmissió lingüística intergeneracional - Brauli Montoya Abat (Caplletra: Revista Internacional de Filologia, 2015)
The article deals with the different kinds of speakers that emerge when language transmission failure arises between consecutive generations. The case is exemplified through the speech community of the city of Alacant, where we can distinguish four kinds of speakers, from the ones who know very well the local variety of Catalan to the ones who only understand this variety and whose first language is Spanish. In between we have the main concern of our study, the precarious speakers, distributed in two categories according to their skill in the use of Catalan, which has become their second language.